"Spokes in the wheel" and how policy gains can diversify a social movement. (3rd May 2020) - Evans, Erin M.
ABSTRACT: Activists often use their resources to pursue protective legislation, like anti-discrimination or environmental protection laws, and the results are often compromised versions of what they wanted. This process of political institutionalization requires ongoing and robust mobilization to strengthen these resulting policies or prevent them from being rescinded all together. Therefore, to understand the pros and cons of political institutionalization we must understand the recursive effects between policy reform and consequent mobilization. Quantitative and qualitative data on the animal advocacy movement, a movement existing for over a century, are used to explore the effects of policy gains on consequent mobilization and explore whether policy gains were followed by de-escalation of protest forms. The findings indicate that policy gains for animal welfare do not de-escalate mobilization, both in terms of the use of disruptive collective action and proliferation of organizations. The article explores the ways that infighting over the terms of policy reform may be an important factor in diversifying the movement.